Wellness Counseling to Improve the Psychological Well-Being - Nurul Ashfiani; Amin Budiamin; Nandang Budiman (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The changes in the learning system during the COVID-19 pandemic in Indonesia affected the psychological well-being of students. The purpose of this study was to examine the effectiveness of the wellness group counseling to improve students’ psychological well-being at the Madrasah Tsanawiyah in Cianjur, West Java, Indonesia. Psychological well-being in this research is defined as the functioning of individual psychological aspects as indicated by self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life and personal growth. This research uses quantitative approach. It adopted quasi-experimental pre-test post-test control group design and the instrument was adapted from Ryff and Singer (1996). The population of the research is the 8th grade students of Madrasah Tsanawiyah Assa’idiyyah Cianjur Class of 2021/2022 academic year and 14 students as samples with purposive sampling. The research result showed that the wellness group counseling has a significant influence to improve the psychological well-being of the students.